Variability of provitamin A carotenoids in plantain: influence of cultivar, bunch type, maturation stage, and location - Udomkun, Patchimaporn; Masso, C.; Swennen, Rony L.; Assfaw Wossen, Tesfamicheal; Amah, D.; Fotso Kaute, A.; Lienou, J.; Adesokan, Michael; Njukwe, E.; Vanlauwe, Bernard (Elsevier, 2020)
In this study, the effect of ripening stage (R), cultivar (C), bunch type (T), and location (L) on the variability of provitamin A carotenoids (pVACs) in 16 plantain cultivars grown in Cameroon and Gabon was investigated. For the sixteen plantain cultivars, fruits were collected at stages 1 (unripe), 5 (ripe), and 7 (overripe) from three different bunch types (French, False Horn, and True Horn) across 13 locations in Cameroon and Gabon. For all cultivars, the highest concentration of carotenoids was found in ripe pulp (p < 0.05). For bunch type, a higher level of pVACs was observed in the French type compared with the False Horn and True Horn types at all ripening stages. In addition, the concentration of pVACs at each ripening stage varied greatly across locations. In both countries, the interaction between the four factors, particularly between R × C, R × T, R × L, R × C × L, and R × T × L, contributed significantly (p < 0.05) to the variability of pVACs in plantain. Daily consumption of 100 g of ripe plantain could meet 36.2–101.7 % of the dietary reference intakes (DRIs) for children 1–5 years old, 20.7–58.1 % for adult women, and 16.1–45.2 % for adult men. These findings can serve as a guide to reducing vitamin A deficiency (VAD) in Africa.